Objective directions of university theses and dissertations of the College of Political Science at the University of Baghdad An analytical study (Journal of the College of Basic Education, 2022)
The research seeks to identify the objective trends of postgraduate students of the College of Political Science - University of Baghdad for the period from 2000-2012 through the objective trends of theses and university dissertations, and what are the most and least studied topics, while resetting the topics that were previously studied towards topics that serve issues of concern to society and move away from Topics that have been studied a lot in order to avoid repetition, and the research came out after results, the most prominent of which are:The total of what was accomplished in this college is 401 theses and dissertations, and the theses had the largest share of them, as they reached 69%, with 275 theses, compared to 126 theses, or 31%. And the emergence of large differences between the subjects studied within each of the branches in the college.